Examining the Value of Gratitude in Determining Selling Prices - Riyanti; Sofyan Syamsuddin; Darwis Said; Syarifuddin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study attempts to explore and uncover the meaning of determining the selling price of fish traders.This study uses phenomenology as a method with data collection through interviews and documentation. The study shows that fish traders tend to ignore the calculation of the Cost of Goods Sold (COGS). The values ​​of gratitude and love expressed in the COGS are used as the basis for determining the selling price of fish. The low selling price of fish for informants is conceptualized as a "feeling" of mutual love for others. Several non-material aspects underlie the neglect of COGS, such as the attitude of fish traders and collectors who often express gratitude for the results of fish sales. The implied gratitude illustrates the neglect of the cost aspect in COGS in determining the selling price. This study reveals the phenomenon of determining COGS and fish selling prices for fish traders.